Penampilan Reproduksi Sapi Bali pada Peternakan Intensif di Instalasi Pembibitan Pulukan - Mahmud Siswanto; Ni Wayan Patmawati; Ni Nyoman Trinayani; I Nengah Wandia; I Ketut Puja (Udayana University, 2013)
This studi was conducted to investigate the reproductive performances of Bali cattle under intensive management in breeding instalation Pulukan Bali from 2008 to 2010. Totaling 298 2 - 6.5 year old heifers were use to represents the benchmark reproductive performances of Bali cattle. Data collected were age at first heat (AFH), age at first calving (AFC), calving interval (CI), and services per conception (SPC). The overall means for AFH, AFC,and CI were 718.57 ± 12.65; 1104.51 ± 23.82, and 350.46 ± 27.98 days respectively, and SPC was 1.65 ± 0.87.